The Linkage of Business Community (Case Study of Rattan Industries in the Village of Trangsan, Gatak, Sukoharjo) - Priyono Priyono; Dilahur Dilahur; Choirul Amin; Isti’ana Maftuchah; Dina Syafrianingsih (Forum Geografi, 1999)
Indonesian industry is likely to snap because it relies on the monopolitic conglomerate’s industry so that it cause the inter relationship between big and smaller units of industry to become weak. The weakness of the industrial relationship is caused by the units independetly. This is different from the industry which is based on community concept emphasizing a main priority to close inter relationship between the units. This research was arried out in Trangsan, Gatak, Sukoharjo, Central Java. Where there is a industrial community which has been a close inter relationship since long time ago. The goal of this research is to know the type and the nature of unit inter relationship in rattan industrial community in Trangsan, and know the strategy how it faced a nationally economical crisis.This research used a survei method. The number of the population was 110 entrepreneurs from Trangsan. The sample was obtained with stratied into three categories, based on number of labour force. Every category was taken 20% as sample based on homogeneity sample, ana the respondent was examined with random sampling. The collected data were presented in frequency and cross table. The analysis of qualitative data used logical rationale, deductive – inductive, analogy and comparison, while the analysis of quantitative data used the analysis of frequency and cross table. The use of these two analysis was the result of the research.These are the result of the research: 1) a inter relationship among small – scalled businesses; 2) there is a weak inter relationship between small and medium scaled industries; 3) the business inter relationship of rattan industries is subcontract in which a part of the big scaled industry’s job is reponsible for the small saled one; 4) the form of the business inter relationship is cooperative; 5) the main strategy of rattan industry community to face nationally economical orisis strengthens their business inter relationship.